Nurses’ challenges during the COVID-19 pandemic: A literature review - Wijaya, Rafika Dora; Permatasari, Henny (Journal of Holistic Nursing Science, 2021)
COVID-19 Pandemic has been a devastating health issue worldwide. This condition impacts all aspects of life including clinical nursing practice at the hospital. Nurses experience various challenges during their duties. However, little is known about investigating these challenges. This study aims at investigating problems facing the nurses in the COVID-19 Pandemic. This study used a literature review study design. Several databases were used as follows Science Direct, Proquest, Sage, and Wiley. The inclusion and criteria were clearly described in this method section. The study documented that there were three main themes: challenges, strategy, and nurses' need in the COVID-19 Pandemic. The study needs further exploration in terms of strategies to deal with the challenges. Keywords: nursing care; pandemic; health challenges; nursing practice